Suitability of Recuperation Industry Development——A Case Study of Sichuan Province, China. (June 2020) - Tang, Jin; Wu, Haoyue; Luo, Luxi; Fu, Gang
Abstract: As an emerging industry, the development of recuperation industry is quite promising, and it's becoming an important support to the transformation of resource-oriented cities, the integration of primary, secondary and tertiary industries in rural areas, and the development of new industries and new businesses in China. In this paper, the studies related to recuperation industry are reviewed, after which the theory of "6+1" is adopted into use for building a comprehensive index system to evaluate the suitability of development of recuperation industry. The results show that places including Chengdu, Liangshan, Panzhihua, Mianyang, Nanchong and Guangyuan are appropriate for developing recuperation industry. Among them, the advantages in supporting facilities of Chengdu lay a good foundation for the development of recuperation industry; sunshine-based and forest-based recuperation suites Panzhihua better; and highland-based recuperation suites Yi Autonomous Prefecture of Liangshan. Places including Suining, Neijiang, Zigong, Aba and Garze are not appropriate for developing recuperation industry. The measurement results, with the development reality of Sichuan considered, provides some references for the development of recuperation industry in Sichuan in future.